Dignity of the calling : educators share the beginnings of their journeys - Kemp, Andrew T. (Emerald Publishing Limited : Information Age Publishing, Inc., 2018)
"Although I was a teacher prior to the entering the professoriate, I was not ready for the gargantuan professional and personal transition to higher education. I was not prepared for minutiae of forms, deadlines of inter-office programs, personalities, and most of all for the human and sometimes illogical relationships among colleagues. I was caught off-guard by the nuanced thinking of students; and most of all, I was, at times, overwhelmed by the time constraints of research, teaching and service on me and my family. However, I survived, and I believe I thrived in in my small slice of the academic world. My experience, although unique to me, was that of many neophyte faculty. The purpose of this Dignity of the Calling is to share other stories of faculty entry into higher education. These stories focus on the deeply personal nature of the new academic. Framed around the idea of curriculum being contextual and how life experience guides what we do, this collection of memoirs, recollections, and personal narratives allows the reader to share these lived experiences"--